English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

pls help! thank you!

2007-02-19 15:15:16 · 4 answers · asked by Chona V 1 in Science & Mathematics Mathematics

4 answers

This becomes (2x-1)(x+2), thus the roots are 1/2 and -2.

2007-02-19 15:20:22 · answer #1 · answered by Hokieman 2 · 0 0

2x^2 + 3x - 2 = (2x - 1 )(x + 2) = 0, therefore

x = 1/2 is a solution. QED

Live long and prosper.

P.S. CHECK: 2(1/2)^2 + 3 (1/2) - 2 = 1/2 + 3/2 - 2 = 2 - 2 = 0. It checks out.

2007-02-19 23:19:42 · answer #2 · answered by Dr Spock 6 · 0 0

factor

(2x-1)(x+2)=0
so x=1/2 and x=-2

2007-02-19 23:21:52 · answer #3 · answered by Rob M 4 · 0 0

2x^2 + 3x-2 = 0
(2x-1)(x+2)=0
2x-1=0
2x=1
x=1/2

x+2=0
x=-2

x=1/2 is 1 of the answers on your list. -2 is not.

2007-02-19 23:55:47 · answer #4 · answered by yupchagee 7 · 0 0

fedest.com, questions and answers